2018
DOI: 10.1021/acs.energyfuels.8b02684
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Process Water Recycling and Particle Sizes on Hydrothermal Carbonization of Biomass

Abstract: Hydrothermal carbonization (HTC) is a promising thermochemical process for the conversion of biomass with high moisture content, and therefore, interest in the development of continuous technology is growing. However, the development of continuous HTC systems requires the in-depth understanding of reaction kinetics, heat transfer mechanisms, exothermic or endothermic nature of the reaction, effect of operational parameters, recyclability of process water, and variability in biomass feedstock. The current paper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
29
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 61 publications
(32 citation statements)
references
References 33 publications
3
29
0
Order By: Relevance
“…More details on the procedure of these characterization tests and the composition of the products can be found in Ref. [15].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…More details on the procedure of these characterization tests and the composition of the products can be found in Ref. [15].…”
Section: Methodsmentioning
confidence: 99%
“…The process water from HTC is acidic and it contains water, acetic acid, and a number of other organic acids [15]. According to Kambo et al [14], these organic acids mainly contain acetic acid, 5-Hydroxyl Methyl Furfural (HMF), and levulinic acid.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Starting from experimental data (relevant to 39 HTC tests), Heidari et al [80] made an attempt to predict the effect of several severity factor values (3.83, 5.01, and 6.19) on the hydrochar mass yield, higher heating value (HHV), and carbon content. With the same aim, in a work dealing with the water recycling effect during the HTC of sawdust, Heidari et al [81] used severity factors between 4.3 and 5.3. Similarly, Basso et al [82] reported the solid, liquid, and gaseous phase yields resulting from HTC of grape marc constituents as a function of the severity factor.…”
Section: Severity and Coalification Modelsmentioning
confidence: 99%
“…However, from this concept, processes with a previously unknown or only partially known input substances composition are beyond the scope. Examples of a such process may be recycling or regeneration processes [1][2][3]. The input substances here can be wasted, polluted, or otherwise contaminated raw materials with a major impact on the system's behaviour, and of course also on the system model and/or model parameters.…”
Section: Introductionmentioning
confidence: 99%